The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12885-020-07240-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis comparing companion diagnostic tests for EGFR, ALK, and ROS1 versus next-generation sequencing (NGS) in advanced adenocarcinoma lung cancer patients

Abstract: Background The treatment of choice for advanced non–small cell lung cancer is selected according to the presence of specific alterations. Patients should undergo molecular testing for relevant modifications and the mutational status of EGFR and translocation of ALK and ROS1 are commonly tested to offer the best intervention. In addition, the tests costs should also be taken in consideration. Therefore, this work was performed in order to evaluate the cost-effectiveness of a unique exam using NGS (next generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
(49 reference statements)
0
27
1
Order By: Relevance
“…The second CEA that we identified was developed from the Brazilian payer perspective; thus, it is difficult to compare and contrast costs directly. 65 In addition, the two CEA models were state-transition models; consequently, we would caution against comparison of the results of our model. In the third economic study that we identified, a budget impact analysis was developed from the Canadian perspective and used a model structure similar to that used in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The second CEA that we identified was developed from the Brazilian payer perspective; thus, it is difficult to compare and contrast costs directly. 65 In addition, the two CEA models were state-transition models; consequently, we would caution against comparison of the results of our model. In the third economic study that we identified, a budget impact analysis was developed from the Canadian perspective and used a model structure similar to that used in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether anti-angiogenesis therapy could improve the prognosis of patients with VM remains to be determined. Now in the world, especially in developing countries, the public health burden caused by cancer is relatively heavy [35]. However, because of the advantages of targeted therapy in perfect disease control and diseasefree survival in lung adenocarcinoma, many guidelines still recommend TKIs as the first-line treatment in EGFR mutated NSCLC [36].…”
Section: Discussionmentioning
confidence: 99%
“…Technical limitations of these platforms and the restrictions imposed by the limited amount of material obtained from biopsies resulted in the development of parallel multi-genic DNA sequencing platforms, such as next-generation sequencing (NGS), which enable the simultaneous analysis of hundreds of genetic alterations in a single test. 36 - 39 The first FDA-approved assay based on NGS was the FoundationFocus CDx BRCA Assay for the detection of BRCA1 and BRCA2 alterations in tissues from ovarian cancer patients potentially eligible for treatment with rucaparib (Rubraca). In 2017, the FDA approved FoundationOne CDx (Foundation Medicine) as the first FDA-approved comprehensive genomic profiling (CGP) assay for all solid tumors incorporating multiple companion diagnostics.…”
Section: State Of the Art For CDXmentioning
confidence: 99%